MiR‐30d is related to asbestos exposure and inhibits migration and invasion in NCI‐H2452 cells. Issue 10 (30th August 2017) - Ju, Li; Wu, Wei; Yin, Xianhong; Xiao, Yun; Jia, Zhenyu; Lou, Jianlin; Yu, Min; Ying, Shibo; Chen, Tianhui; Jiang, Zhaoqiang; Li, Wei; Chen, Junqiang; et al.
Abstract : Pleural malignant mesothelioma (MM) is a highly aggressive tumor that is typically related to asbestos exposure and has a latency of 20–60 years. Several microRNA contribute to MM initiation and progression, but the mechanisms are not clear. Here, we found that miR‐30d is downregulated in the pleural MM cell line NCI‐H2452, in the plasma of asbestos‐exposed individuals, and in asbestos‐exposed mesothelial cells. Furthermore, we investigated the influence of the overexpression of miR‐30d in pleural MM cells. We demonstrated that miR‐30d overexpression could suppress pleural MM cell proliferation, migration, and invasion in vitro and could promote cell apoptosis but could not significantly influence cell cycle. The mRNA and protein expression of vimentin and TWIST1 decreased, and the mRNA expression of CDH1 increased in NCI‐H2452 cells that overexpressed miR‐30d. We therefore conclude that miR‐30d is related to asbestos exposure and inhibits cell migration and invasion by regulating the epithelial–mesenchymal transition in NCI‐H2452 cells. Abstract : Pleural malignant mesothelioma (MM) is a highly aggressive tumor that is often related to previous exposure to asbestos. We investigated the role of miR‐30d in MM and found this microRNA downregulated in the pleural MM cell line NCI‐H2452, in the plasma of asbestos‐exposed individuals, and in asbestos‐exposed mesothelial cells. Conversely, overexpression of miR‐30d suppressed pleural MM cell proliferation, migration, and invasion in vitro and promoted cell apoptosis but did not significantly influence cell cycle.